INCREASING STUDENT INTEREST IN CITIZENSHIP EDUCATION THROUGH INTERACTIVE MULTIMEDIA BASED LEARNING AT SDN BAGOR - Wahyu Triandani; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The progress of data and correspondence innovation (ICT) is currently closely connected with the times that are always present bringing change. This innovation is aimed at leading to positive changes in teaching and learning activities. The implementation of citizenship learning for grade 5 students at SDN Bagor is in accordance with the standard of the education process, but is not yet optimal. When carrying out learning, compared to the use of media in other subjects, conventional media in the form of images are still used in Civics subjects. This implies that Civics learning has not kept up with the times. For this reason, interactive multimedia-based learning is held in Civics lessons. The method used is Classroom Action Research, also known as CAR (Classroom Action Research). Data collection methods used in this study were observation, questionnaires, and interviews. The results of the study stated that there was an effect of the application of interactive multimedia-based learning in Civics learning on the interest of 5th graders at SDN Bagor.